Pengaruh Penambahan Minyak Jagung Pada Pembuatan Keju Olahan (Sliced cheese) Dengan Koagulan Getah Pepaya Kering Terhadap Kekerasan (Hardness), Waktu Leleh dan Akseptabilitas - Khoppipah, Fitri Anti Siti; Putranto, Wendry Setiyadi; Wulandari, Eka (Unpad Press, 2025)
Sliced cheese refers to a type of processed cheese that iseither molded or cut into thin slices. The addation of corn oil intoprocessed cheese formulations is anticipated to enhance thephysical properties, overall quality, and acceptability of slicedcheese products. The objective of this study was to investigate theimpact of varying concentrations of corn oil on specific attributesof sliced cheese, namely hardness, melting time, and sensoryacceptability. An experimental approach was employed, utilizing aCompletely Randomized Design (CRD) with four levels of corn oiladdition: P0 (0%), P1 (5%), P2 (10%), and P3 (15%), with eachtreatment replicated five times. Data obtained from physicalanalyses were subjected to Analysis of Variance (ANOVA). In theevent of statistically significant differences, Duncan's MultipleRange Test was applied. Sensory acceptability data were evaluatedusing the Kruskal-Wallis test, and when necessary, furtheranalyzed with the Mann-Whitney U test. The results indicated thatthe treatment with 15% corn oil (P3) significantly affected meltingtime (P < 0,05), yielding a melting duration of 13.56 minutes.However, corn oil addition did not significantly influence hardness(P > 0,05), which measured 60,08 N/m², nor did it affectacceptability. Sensory scores for color 3,90 (liked), aroma 3,85(liked), texture 3,55 (liked), taste 3,35 (liked), and total acceptance3,50 (liked).